2021
DOI: 10.1186/s12967-021-02857-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the functions of two biomarkers in human oligodendrocyte progenitor cell development

Abstract: Background Human oligodendrocyte precursor cells (hOPCs) are an important source of myelinating cells for cell transplantation to treat demyelinating diseases. Myelin oligodendrocytes develop from migratory and proliferative hOPCs. It is well known that NG2 and A2B5 are important biological markers of hOPCs. However, the functional differences between the cell populations represented by these two biomarkers have not been well studied in depth. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, this approach that contains the initial xenografts before complete immune development of the host and the second xenografts derived from the same species of the initial one did not always result in long-term xenograft survival which depends on the species of donor, the origin of the cells, 3 , 6 , 7 and the strain of the host. 21 There are reports of failure to induce immune tolerance after desensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach that contains the initial xenografts before complete immune development of the host and the second xenografts derived from the same species of the initial one did not always result in long-term xenograft survival which depends on the species of donor, the origin of the cells, 3 , 6 , 7 and the strain of the host. 21 There are reports of failure to induce immune tolerance after desensitization.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Transplantation of exogenous hOPCs can effectively promote myelin repair. 6 For example, transplanting hOPCs into neonatal Shiverer mice can promote cerebral myelination in congenital demyelination 7 ; embryonic stem cell (ESC)-derived OLs transplanted into Sprague-Dawley (SD) rats can migrate into white matter and repair white matter structure and function 8 ; transplantation of hOPCs restored neurobehavioral functions by preventing axonal demyelination in SD rats. 9 hOPCs can be used in the cell therapy of perinatal hypoxic-ischemic and infectious brain injuries, including periventricular leukomalacia and cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, hNSCs were isolated from the cortex of human embryos aged 10–13 weeks and amplified in the NSC medium. To generate hOPCs, hNSCs were cultured for 10 days to form neurospheres, which were dissociated into single cells and induced to differentiate in the differentiation medium ( 19 ). The purity of the hOPCs was 80–90%, as confirmed in our previous study ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are, however, some studies focusing on cells expressing these markers but they mainly concern in vitro experiments. As an example, Zhou et al [71] have characterized A2B5+, A2B5-, NG2+ and NG2-cells obtained from NSCs derived from the human fetal brain after in vitro differentiation into OPCs. In the whole cell population, flow cytometry demonstrated that PDGFRα expression was recorded on up to 75% of the cells, whereas A2B5+ cells accounted for approximately 26% and NG2 for 15%.…”
Section: A2b5 and Other Opc Cell Surface Markers: Ng2 And Pdgfrαmentioning
confidence: 99%